2019
DOI: 10.1103/physrevd.100.023523
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the density profiles of the first halos

Abstract: The first dark matter halos form by direct collapse from peaks in the matter density field, and evidence from numerical simulations and other analyses suggests that the dense inner regions of these objects largely persist today. These halos would be the densest dark matter structures in the Universe, and their abundance can probe processes that leave imprints on the primordial density field, such as inflation or an early matter-dominated era. They can also probe dark matter through its free-streaming scale. Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 155 publications
0
48
0
Order By: Relevance
“…Finally, another interesting question concerns the internal structure of WDM halos near the free streaming scale. As in the case of neutralino simulations, simulations have found indications that WDM halos have inner density profiles that are steeper than their CDM counterparts (Colı ´n et al 2008;Polisensky and Ricotti 2015;Ogiya and Hahn 2018;Delos et al 2019).…”
Section: Warm Dark Matter (Wdm)mentioning
confidence: 93%
See 1 more Smart Citation
“…Finally, another interesting question concerns the internal structure of WDM halos near the free streaming scale. As in the case of neutralino simulations, simulations have found indications that WDM halos have inner density profiles that are steeper than their CDM counterparts (Colı ´n et al 2008;Polisensky and Ricotti 2015;Ogiya and Hahn 2018;Delos et al 2019).…”
Section: Warm Dark Matter (Wdm)mentioning
confidence: 93%
“…In contrast, most neutralino simulations find that the initial internal structure of microhalos is better described by a single power law profile $ r À1:5 , as first pointed out by Diemand et al (2005) (see also Ishiyama et al 2009;Anderhalden and Diemand 2013;Ishiyama 2014;Ogiya et al 2016;Angulo et al 2017;Delos et al 2019). This very steep profile would make microhalos very resilient to tidal disruption by the Milky Way or by binary stars and also would enhance their corresponding emission from dark matter self annihilation, making them potentially detectable by future experiments (Diemand et al 2006;Ishiyama et al 2009;Ishiyama 2014;Delos 2019), although their abundance is affected by free streaming (Ishiyama and Ando 2020).…”
Section: Weakly-interacting Massive Particlesmentioning
confidence: 96%
“…The peak scale is determined by the cut-off scale in the matter power spectrum, so the formation time of the first halos is most sensitive to the ratio k cut /k reh , with only a weak dependence on the reheat temperature [43,359]. The formation time of a halo determines its density, and Delos et al [634] demonstrated that the density profiles of these first halos can be predicted directly from ∆ 2 (k).…”
Section: The Microhalo Populationmentioning
confidence: 99%
“…Ref. [634] showed that microhalo profiles and their abundance can be predicted in a simple way from properties of the precursor linear density field, enabling rapid computation of Γ/M in a given cosmological scenario [824]. Other works [359,358,360] have employed Press-Schechter theory [635] to characterize microhalo populations and assumed that these microhalos have NFW profiles with low concentrations at formation.…”
Section: Dark Matter Annihilation Within Microhalosmentioning
confidence: 99%
“…The secondary infall models also predicts the full density profile inside and outside the splashback radius, but it is well known that these predictions are not realistic, at least not unless the model is coupled with collapse from cored peaks (e.g., Dalal et al 2010;Ogiya & Hahn 2018;Delos et al 2019), realistic accretion histories (Lu et al 2006), or mergers (Ogiya et al 2016;Angulo et al 2017). One reason is that, by itself, the model can predict only power-law density profiles because it evolves a self-similar initial density perturbation.…”
Section: Can We Predict the Slope Of The Orbiting Term?mentioning
confidence: 99%